RISK FACTORS OF THE NURSING DIAGNOSIS IN THE SAFETY/PROTECTION DOMAIN: INTEGRATIVE REVIEW - Laísla Alves Moura; Jéssica Naiara de Medeiros Araújo; Danielly Oliveira Pitombeira; Ana Paula Nunes de Lima Fernandes; Fabiane Rocha Botarelli; Allyne Fortes Vitor (Universidade Federal do Paraná, 2016)
Integrative review to summarize the available evidence in the literature on the risk factors for the nursing diagnoses in the Safety/Protection Domain and correlated adverse events in hospitalized patients. Undertaken in February 2015 through a search in the databases Cumulative Index to Nursing and Allied Health, Literatura Latino-americana e do Caribe em Ciências da Saúde, National Library of Medicine National Institutes of Health, Scientific Electronic Library Online and Scopus, which resulted in 19 studies. The most prevalent risk factors were: extended hospitalization, advanced age and burden of nursing professionals. The category Risk for injury presented the largest number of risk factors without correspondence in NANDA International (NANDA-I), while the category Risk for falls presented the largest number of equivalents. Thus, the presence of the risk factors cited in the literature without inclusion in NANDA-I indicates the need for more in-depth studies on the theme.